Control interno de los activos del área de bodega y su impacto en la información financiera del gobierno autónomo descentralizado del cantón El Empalme, año 2013 - Navia Sabando, Lisandro Jacinto (2015)
The present research proposal essentially aims to evaluate internal control winery area and its impact on the financial information of Decentralized Autonomous Government of El Empalme Cantón in 2013. The development and implementation of the study did on the premises of Decentralized Autonomous Government of El Empalme Canton, located at Av Quevedo citadel May 2, which had the following objectives:. To analyze the reliability of financial reporting, assessing the efficiency and effectiveness of operations and determine compliance with the regulations applicable to the storage area of GAD Cantón El Empalme. To fulfill the objectives of internal control program was structured: Phase I Planning Internal Control Implementation Phase II Phase III Internal Control and Communication Results, whose results showed improper use of standards that assets are safeguarded that body. The hypotheses are accepted because they facilitated the review of the legal framework for judging compliance processes and regulatory guidelines; evaluation of internal control was performed with substantive evidence and documents that revealed the weaknesses in the flowchart of warehouse area and supervision that were transcribed in the accompanying report. Among the findings is the deficiency in process inventory built in the area of Bodega, why not corrective measures and decisions that favor the performance of the entity is taken.